Modeling the Relationship Between Service Encounter and Customer Satisfaction through Perceived Value As a Mediator Variable and Personal Variables As Moderator Variables Using SEM PLS - Khamet, Saadia; Bessa, Sami; Abdelhamid, Fadhila (Jordan Journal of Business Administration, 2025)
This study aims to test the causal relationship between service encounter and customer satisfaction through perceived value as a mediator variable. We will rely on the deductive method to test the direct and indirect relationships between variables, including the adjustment relationship for personal variables in the relationship between perceived value and service encounter and customer satisfaction. Three hundred (300) questionnaire forms were distributed to a sample of patients in public and private hospitals in Bouira, Algeria. The collected data is analyzed using modeling of structural equations based on partial least squares. One of the most important results of the study is the existence of an indirect relationship between service encounter and customer satisfaction in terms of perceived value, where the type of mediation is partial supplementary, with the effect of adjusting the scientific level to positively strengthen the relationship between both service encounter and perceived value with customer satisfaction. Conversely, there is no adjustment effect for both gender and age.